Early redox activities modulate Xenopus tail regeneration. Issue 1 (December 2018) - Ferreira, Fernando; Raghunathan, VijayKrishna; Luxardi, Guillaume; Zhu, Kan; Zhao, Min
Abstract Redox state sustained by reactive oxygen species (ROS) is crucial for regeneration; however, the interplay between oxygen (O2 ), ROS and hypoxia-inducible factors (HIF) remains elusive. Here we observe, using an optic-based probe (optrode), an elevated and steady O2 influx immediately upon amputation. The spatiotemporal O2 influx profile correlates with the regeneration ofXenopus laevis tadpole tails. Inhibition of ROS production but not ROS scavenging decreases O2 influx. Inhibition of HIF-1α impairs regeneration and stabilization of HIF-1α induces regeneration in the refractory period. In the regeneration bud, hypoxia correlates with O2 influx, ROS production, and HIF-1α stabilization that modulate regeneration. Further analyses reveal that heat shock protein 90 is a putative downstream target of HIF-1α while electric current reversal is a de facto downstream target of HIF-1α. Collectively, the results show a mechanism for regeneration via the orchestration of O2 influx, ROS production, and HIF-1α stabilization. Reactive oxygen species (ROS) and hypoxia-inducible factors (HIF) mediate regeneration but how is unclear. Here, the authors use an optic-based probe ('optrode') to monitor oxygen (O2 ) duringXenopus tail regeneration, identifying crosstalk between O2 influx, ROS production, and HIF-1α stabilization.